2016
DOI: 10.1038/srep36270
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of High Fasting Insulin and Insulin Resistance Among Overweight/Obese Adolescents

Abstract: Hyperinsulinaemia is the earliest subclinical metabolic abnormality, which precedes insulin resistance in obese children. An investigation was conducted on the potential predictors of fasting insulin and insulin resistance among overweight/obese adolescents in a developing Asian country. A total of 173 overweight/obese (BMI > 85th percentile) multi-ethnic Malaysian adolescents aged 13 were recruited from 23 randomly selected schools in this cross-sectional study. Waist circumference (WC), body fat percentage (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 44 publications
3
30
1
1
Order By: Relevance
“…Other studies reported these difference among obese males and females to be not significant. [34,35] However, our results show that the prevalence of abnormal plasma glucose 2 hours after the performance of oral glucose tolerance test did not reveal significant differences between boys and girls. Another larger cross-sectional study found significantly higher prevalence of elevated blood glucose in participants with severe obesity.…”
Section: Discussioncontrasting
confidence: 70%
“…Other studies reported these difference among obese males and females to be not significant. [34,35] However, our results show that the prevalence of abnormal plasma glucose 2 hours after the performance of oral glucose tolerance test did not reveal significant differences between boys and girls. Another larger cross-sectional study found significantly higher prevalence of elevated blood glucose in participants with severe obesity.…”
Section: Discussioncontrasting
confidence: 70%
“…The benefit of reducing excess adiposity in youth to prevent T2D is supported by prospective studies that demonstrate BMI in childhood predicts incident T2D in adulthood whereas youth with obesity who are able to normalize their weight in adulthood exhibit similar T2D risk profiles as adults who never had obesity . Body fat is strongly associated with insulin resistance and beta‐cell dysfunction among adolescents . Further, greater accumulation of abdominal fat is associated with a decline in metabolic health, specifically greater visceral adipose tissue is associated with reduction in beta‐cell function and higher trunk fat is correlated with insulin resistance .…”
Section: Discussionmentioning
confidence: 99%
“…In adults, CRF is regarded as a predictor of general mortality and it is negatively correlated with hypertension and diabetes [7][8][9][10][11][12][13]. Low CRF in young people is related e.g., to obesity, which increases the risk of cardiovascular diseases [14] and metabolic syndrome characteristics [15,16]. Studies have also revealed that improved CRF leads to better health results regardless of body mass index (BMI) [9].…”
Section: Introductionmentioning
confidence: 99%